2019
DOI: 10.1016/j.bmcl.2018.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Fluoromethylcyclopropylamine derivatives as potential in vivo toxicophores – A cautionary disclosure

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In contrast, a total of 24 non-fluorinated compounds were well-tolerated across doses ranging from 5 to 160 mg/kg. Collectively, these results implicated a common metabolite of the fluorinated derivatives as the ultimate toxicant, although the metabolic pathway was not elucidated …”
Section: Fluorinated Aminesmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, a total of 24 non-fluorinated compounds were well-tolerated across doses ranging from 5 to 160 mg/kg. Collectively, these results implicated a common metabolite of the fluorinated derivatives as the ultimate toxicant, although the metabolic pathway was not elucidated …”
Section: Fluorinated Aminesmentioning
confidence: 98%
“…Unexpected but strongly adverse effects were associated with oral administration of poly-ADP ribose glycohydrolase (PARG) inhibitors incorporating an N-(1-(fluoromethyl)cyclopropyl)sulfonamide substructure, with observations suggesting a role for gut metabolism on the basis of the absence of toxicity following iv dosing. 274 As background, 335 and 336 exhibited short half-lives in vivo that precluded evaluation in animal efficacy models. Subsequent in vitro studies identified the sulfonamide substituent as the major site of metabolism, giving rise to the primary sulfonamide (RSO 2 NH 2 ).…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have provided preclinical evidence that CCNE1 could be a predictive biomarker for a response to PARGi in breast cancer. To date, no PARGi has entered the clinic and no in vivo inhibitors has been identi ed yet, potentially owing to poor pharamacokinetic and phamracodynamic properties in vivo including a short half-life and lack of sustained target coverage 37 . Further work will be required to optimize this class of compounds for use in vivo and ultimately for use in the clinic.…”
Section: Discussionmentioning
confidence: 99%